Regulation of IRF-3-dependent innate immunity by the papain-like protease domain of the severe acute respiratory syndrome coronavirus - Devaraj, Santhana G; Wang, Nan; Chen, Zhongbin; Chen, Zihong; Tseng, Monica; Barretto, Naina; Lin, Rongtuan; Peters, Clarence J; Tseng, Chien-Te K; Baker, Susan C; Li, Kui (The Journal of biological chemistry, 2007)
Severe acute respiratory syndrome coronavirus (SARS-CoV) is a novel coronavirus that causes a highly contagious respiratory disease, SARS, with significant mortality. Although factors contributing to the highly pathogenic nature of SARS-CoV remain poorly understood, it has been reported that SARS-CoV infection does not induce type I interferons (IFNs) in cell culture. However, it is uncertain whether SARS-CoV evades host detection or has evolved mechanisms to counteract innate host defenses. We show here that infection of SARS-CoV triggers a weak IFN response in cultured human lung/bronchial epithelial cells without inducing the phosphorylation of IFN-regulatory factor 3 (IRF-3), a latent cellular transcription factor that is pivotal for type I IFN synthesis. Furthermore, SARS-CoV infection blocked the induction of IFN antiviral activity and the up-regulation of protein expression of a subset of IFN-stimulated genes triggered by double-stranded RNA or an unrelated paramyxovirus. In searching for a SARS-CoV protein capable of counteracting innate immunity, we identified the papain-like protease (PLpro) domain as a potent IFN antagonist. The inhibition of the IFN response does not require the protease activity of PLpro. Rather, PLpro interacts with IRF-3 and inhibits the phosphorylation and nuclear translocation of IRF-3, thereby disrupting the activation of type I IFN responses through either Toll-like receptor 3 or retinoic acid-inducible gene I/melanoma differentiation-associated gene 5 pathways. Our data suggest that regulation of IRF-3-dependent innate antiviral defenses by PLpro may contribute to the establishment of SARS-CoV infection.